Online Delivery Of Programmes: A Case Study Of IGNOU - Sharma, Ramesh (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2001)
Online education is the most exciting segment in the Indian IT space. A host of e-education sites continue to enter the market with focused offerings, linking up students and teachers, almost on a daily basis. This is happening because the new medium seeks to supplement -- not replace -- traditional teaching-learning methodologies. Keeping in view the global and in country/domestic market changes, India has to play a vital role in terms of software exports, skilled manpower support, and online education. With India currently in the midst of a "dotcom" wave, Indira Ghandi National Open University (IGNOU) has taken the initiative in launching online in January 2000 two of its educational computer programmes. In July 2000 it launched twenty capsule courses (each comprising three courses) in different specialization areas of management [http://www.ignou.com/index.htm]. Each of these capsules addresses one specific functional or specialization area, one basic course pertaining to that specialization and a project course. The Bachelor of Information Technology and Advanced Diploma in Information Technology programmes are offered through a Virtual Campus Initiative (VCI). Management Programme capsule courses are offered through Project MEIDS (Management Education through Interactive Delivery Systems).